Elaboração e implementação de um protótipo de esteira seletora por cor - Queiroz, Mariana Emer de (2017)
The present work focuses on the elaboration of a prototype of a color selective mat, which aims to make such separation more efficient than when done manually. For this, the project was elaborated considering the coupling of three elements: a dispenser with 180ᴼ servomotor, where the confections are initially deposited one at a time; The treadmill with a DC motor of 12 V (drives the set) and with a sensor TCS230 (responsible for color recognition); And the pots, which are rotated according to the color identification of the sweets, through the movement performed by a 180ᴼ servomotor. Colored candies of the brand M&M’s® were used as test objects. All of these items were controlled by an Atmega328 microcontroller, using an algorithm initially to register the RGB of the confectionery and subsequently such information was placed in the final code. With the use of this algorithm, the tests were performed and it was possible to observe the influence of light on the detection, so we chose to use the fluorescent lamp. Based on such results, tests were performed to determine the errors, correctness and the amount of confection separated per minute. The experiments were performed with two color recognition sensors with the same configuration. When using the first sensor, a percentage of hits of 94% and a separation rate of 17 confections per minute were obtained. Already in carrying out the same test with the sensor increased the number of hits to 99.4%, and the speed of separation was maintained in 17 confections per minute. This difference in results between sensors 1 and 2 could have been caused by some problem in the sensor photodiode array, since the behavior of the sensor differed in each case. Relating all the possible characteristics and considered as prototype built as being functional.